The European Union and Fundamental Rights/Human Rights: Vanguard or Villain? - Rosas, Allan (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The protection of fundamental rights and human rights in the European Union has witnessed several phases and fluctuations. In the early days of European integration, whilst it would be exaggerated to brand the then Communities a ‘villain,’ there was no explicit recognition of fundamental rights/human rights as being part of Community law. I hope it should have become clear by now that the Union does not fit particularly well into any of these two extremes. But by comparison to the other EU institutions, the Court of Justice has been somewhat of a forerunner, taking the first steps towards a fundamental rights system already in 1969 and contributing in many respects to its further development.